2017
DOI: 10.1002/oby.21838
|View full text |Cite
|
Sign up to set email alerts
|

Normal‐weight obesity and cardiometabolic risk: A 7‐year longitudinal study in girls from prepuberty to early adulthood

Abstract: Children and adolescents with normal body weight and high body fat percentage may be at increased risk for cardiometabolic morbidity in adulthood. Body fatness may be of utility in clinical practice to effectively identify children and adolescents at risk and to permit recommendation of lifestyle changes that could translate to lower risks of cardiovascular diseases in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 38 publications
3
42
0
3
Order By: Relevance
“…Others have reported that normal weight children who present with cardiometabolic risk factors have higher adiposity levels [30]. Similarly, a longitudinal study of girls followed into young adulthood reported that BMI-defined normal weight girls who had a higher percent body fat mass were more likely to develop cardiometabolic risk factors compared to those with a normal weight and a lower percent body fat mass [31]. In adults, it was also shown that NWMU women have a higher percentage of body fat [7].…”
Section: Discussionmentioning
confidence: 97%
“…Others have reported that normal weight children who present with cardiometabolic risk factors have higher adiposity levels [30]. Similarly, a longitudinal study of girls followed into young adulthood reported that BMI-defined normal weight girls who had a higher percent body fat mass were more likely to develop cardiometabolic risk factors compared to those with a normal weight and a lower percent body fat mass [31]. In adults, it was also shown that NWMU women have a higher percentage of body fat [7].…”
Section: Discussionmentioning
confidence: 97%
“…The high prevalence of NWO in both male and female students was in contrast to a Swiss study in adults (aged 35–75 years), which showed a much lower prevalence of NWO of only 5.4% in women and less than 3% in men [ 37 ]. However, in a Finnish study of young women (mean age = 18 years), the prevalence of NWO was estimated to be 39.0% [ 38 , 39 ]. Our results concerning the prevalence of NWO in women were similar to a study of normal weight central obesity in South Africa [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, low grade chronic whole body inflammation, measured by high Hs-CRP, was detected in adolescents with a high body fat %, as previously described in obese adolescents [ 15 , 16 ]. Collectively, these data indicate that these girls with a BMI <85th percentile and a high body fat % have an increased risk of cardiovascular disease [ 14 , 35 , 36 ] as recently described in a Finish seven-year longitudinal study in children and adolescent girls with normal BMI, but high body fat % [ 37 ].…”
Section: Discussionmentioning
confidence: 67%